Comunidade de larvas de Dipteras e qualidade da água e do sedimento em lagoas marginais do Rio Teles Pires - Oliveira, Franciele Fernanda de (2021)
The quality of aquatic environments has become a focus of concern for researchers and managers due to the water demand in human activities, the changes caused by these demands and the importance of conservation and recovery of these ecosystems. In the Teles Pires River Basin, an important tributary of the Amazon Hydrographic Region, where agricultural activity is predominant, studies on the benthic community and the quality of the sediment are rare. In this work we aimed to evaluate the Diptera community and the water and sediment quality in two lakes along the Teles Pires River, in the southern portion of the Amazon Hydrographic Region. Organisms were identified to the lowest taxonomic order when possible, analyzing the physical and chemical parameters of granulometry, physical and chemical parameters of water quality, and the factors that influenced these organisms, in particular the order Diptera, through multivariate analysis (Analysis redundancy - RDA). The results showed that there is temporal variation in Diptera communities in the dry season, the density and richness were higher, and the granulometry influences the composition of these organisms, the parameters PH, dissolved oxygen and total phosphorus showed a strong association with most of organisms, in this sense, the importance of conserving marginal lakes for the maintenance of aquatic biodiversity is highlighted. The scarcity of scientific production in the Teles Pires watershed related to benthic macroinvertebrates, makes this work a background for the middle Teles Pires region before the formation of the UHE Sinop reservoir, and serving as a management tool and guiding future decisions. conservation and uses of water.